Effect of Canopy Cover Level of Cacao and Shade Trees on Splash Erosion On Cacao Land - Suhardi Suhardi; Ahmad Munir; Muhammad Tahir Sapsal; Sitti Nur Faridah; Iqbal Iqbal; Syahrial Sabaniah (The University of Lampung, 2024)
In smallholder cacao plantations, the protective crops used varied, so they have different effects on splash erosion. The management of land cover with a canopy of cacao and shade trees on cacao fields, aims to control of splash erosion. This study was conducted by directly measuring the magnitude of splash erosion under several levels of canopy cover. The magnitude of splash erosion was determined by measuring the depth of the eroded soil using the bottle cap method. The measurements were carried out every rain event (46 rain events with rainfall varied from 0.28 to 97.04 mm). The canopy cover level was determined by analyzing the images taken using a digital camera. The images were processed by Matlab software with closure approach. The data were analyzed by regression analysis to determine the relationship between canopy cover level and the depth of splash erosion that occurred. The results showed that the level of canopy cover influence the depth of splash erosion. In addition, this study indicates that the level of splash erosion not only influenced by the level of closure and rainfall, but also strongly influenced by the size of the leaf cover. Keywords: Cacao plantation, Canopy cover, Regression analysis, Splash erosion.